Visible-Light-Promoted Iridium(III)-Catalyzed Acceptorless Dehydrogenation of N‑Heterocycles at Room Temperature - Mejuto, Carmen; Ibáñez-Ibáñez, Laura; Guisado-Barrios, Gregorio; Mata, Jose A. (ACS catalysis, 2022)
An effective visible-light-promoted iridium(III)-catalyzed hydrogen production from N-heterocycles is described. A single iridium complex constitutes the photocatalytic system playing a dual task, harvesting visible-light and facilitating C–H cleavage and H2 formation at room temperature and without additives. The presence of a chelating C–N ligand combining a mesoionic carbene ligand along with an amido functionality in the IrIII complex is essential to attain the photocatalytic transformation. Furthermore, the IrIII complex is also an efficient catalyst for the thermal reverse process under mild conditions, positioning itself as a proficient candidate for liquid organic hydrogen carrier technologies (LOHCs). Mechanistic studies support a light-induced formation of H2 from the Ir–H intermediate as the operating mode of the iridium complex.